2013
DOI: 10.1016/j.chom.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Initial Symbiont Contact Orchestrates Host-Organ-wide Transcriptional Changes that Prime Tissue Colonization

Abstract: SUMMARY Upon transit to colonization sites, bacteria often experience critical priming that prepares them for subsequent, specific interactions with the host; however, the underlying mechanisms are poorly described. During initiation of the symbiosis between the bacterium Vibrio fischeri and its squid host, which can be observed directly and in real time, ~5 V. fischeri cells aggregate along the mucociliary membranes of a superficial epithelium prior to entering host tissues. Here we show that these few early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
197
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(204 citation statements)
references
References 47 publications
(58 reference statements)
6
197
1
Order By: Relevance
“…1D). Collectively, the data are consistent with a model wherein chitin particles within host hemocytes are released into the crypts and become accessible to extracellular hydrolysis by both host and symbiont chitinases (21,24,36).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…1D). Collectively, the data are consistent with a model wherein chitin particles within host hemocytes are released into the crypts and become accessible to extracellular hydrolysis by both host and symbiont chitinases (21,24,36).…”
Section: Resultssupporting
confidence: 74%
“…The symbiont induces postembryonic light-organ development (19), and the organ morphology reaches maturity in 4 wk (20). Host-derived chitin, a polymeric glycan of N-acetylglucosamine, is known to promote the speciesspecific colonization of the squid by V. fischeri (21). Chitin is synthesized by several types of squid tissue, including macrophage-like immune cells called hemocytes (22) (Fig.…”
Section: Significancementioning
confidence: 99%
“…For experimental inoculation of E. scolopes bacterial concentrations of 10 3 -10 6 cfu/mL are typically used (14,15). It was demonstrated that higher inoculum concentrations led to a greater diversity of strains within the light organ, so we used an inoculum of 2 × 10 5 cfu/mL (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…While the authors tested T6SS1-deficient mutants in vitro, no such data were presented under in vivo conditions. It is well established that chitin-degradation products play a key role in the establishment of the V. fischeri-squid symbiosis (16). As chitin-degradation products induce the T6SS in V. cholerae (12,13), it is conceivable that the same holds true for the T6SS1 of V. fischeri.…”
mentioning
confidence: 86%